(3JaSjQ CHj GddjK GdSeQbfOi GdTGaYis - (3CHh GddjK GdSeQbfOj GdTGaYjs
(3ChdgG (B:s
(3jHJOF HJaSjQ Ghd ShQI GdGYQGa s
(3BNQgG (B:s
(3jfJgi HBNQ ShQI Gdcga s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdNWjH HGdbOS s
Keywords: (3GdJaSjQ hYdhe GdbQBfs